If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -5x = 12 + -1(6x + 7) Reorder the terms: 9 + -5x = 12 + -1(7 + 6x) 9 + -5x = 12 + (7 * -1 + 6x * -1) 9 + -5x = 12 + (-7 + -6x) Combine like terms: 12 + -7 = 5 9 + -5x = 5 + -6x Solving 9 + -5x = 5 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -5x + 6x = 5 + -6x + 6x Combine like terms: -5x + 6x = 1x 9 + 1x = 5 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 1x = 5 + 0 9 + 1x = 5 Add '-9' to each side of the equation. 9 + -9 + 1x = 5 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 5 + -9 1x = 5 + -9 Combine like terms: 5 + -9 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 5.6-0.32x=1.12 | | x+(x-35)+.5x+(x-46)=360 | | 12x+7-4=11x-2 | | 3p^2+10p-8=0 | | -7y+7=-8y+6 | | -4s+32=0 | | x+5+4x+7=27 | | 27n=-15 | | 3x+y=7 | | 31=-53-14i | | 2x+6=3x+2 | | -12n+7=-5 | | 2g+3=23-(2g-6) | | 3+4(x+2)-2x= | | 7y-28x-63=0 | | 7b-2-12b=63 | | 11-c=178 | | 6y-20=2y-4 | | 36=8-14d | | 57.99+0.11x=58.54 | | 6(5x+7)=28x-0 | | 4x-5(3x+10)=12 | | 7-3(-4k+2k)= | | 12x-5=6x+19 | | 2n-4=8 | | 3n+1.75=22.75 | | 14x-21=31(4x-11) | | 2n-5=11 | | w+(-4.1)=-5 | | 1-3y+1y=5 | | 2n-10=35 | | 5r+15=0 |